Sistem Pendukung Keputusan Penerima Beras Miskin di Desa Masbagik Selatan Dengan Metode AHP dan TOPSIS - Murgianti, Liana Hapsari; Parwita, Wayan Gede Suka; Lestari, Eka Ayu Purnama (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
The poor rice program is one of the government effort to cope the problem of poverty and keep the people’s food less economically. But in reality the program still not optimal due to at the time of the selection of poor rice recipients there is no support system yet and the absence of accurate calculation at the time of granting poor rice recipients. So that causes all the people get the help of poor rice. This causes poor rice distribution is not right on target. Therefore there is a need for a system that can assist in the recipients of poor rice recipients. In this study the criteria used in the selection of poor rice recipients are age, income, dependent and work. The method used in this study is the method of AHP and TOPSIS. The AHP method is used to determine the weight of the importance of each criteria used, while the TOPSIS method is used to provide the best alternative to get the help of poor rice in Masbagik village. The result of this study indicate that the system has been built as expected according to the test conducted with blackbox testing.